Wafer-scale, highly uniform, and well-arrayed suspended nanostructures for enhancing the performance of electronic devices. Issue 4 (6th January 2022) - Zhao, Zhi-Jun; Ahn, Junseong; Lee, Dongheon; Jeong, Chan Bae; Kang, Mingu; Choi, Jungrak; Bok, Moonjeong; Hwang, Soonhyoung; Jeon, Sohee; Park, Sooyeon; Ko, Jiwoo; Chang, Ki Soo; et al.
Abstract : Wafer-scale, highly uniform, well-arrayed suspended nanostructures play an important role in enhancing the performance of a diverse group of nanodevices. Abstract : Suspended nanostructures play an important role in enhancing the performance of a diverse group of nanodevices. However, realizing a good arrangement and suspension for nanostructures of various shapes remains a significant challenge. Herein, a rapid and simple method for fabricating wafer-scale, highly uniform, well-arrayed suspended nanostructures via nanowelding lithography is reported. Suspended nanostructures with various shapes (nanowires, nanoholes, nanomesh, and nanofilms) and materials (gold, silver, and palladium metals) were employed to demonstrate the applicability of our method. Moreover, gas sensors and thermoacoustic speakers with suspended nanowires outperformed those with unsuspended nanostructures. The proposed method is expected to help advance the development of future nanodevices based on suspended nanostructures.